Effects of Peer-Based Intervention on Prevention Behavior of Sexually Transmitted Infections and Unwanted Pregnancy in Adolescents: A Meta Analysis - Safitri, Denanda Agnes; Rahardjo, Setyo Sri; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background:In facing the transition peri